2008
DOI: 10.1080/13693780801961329
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of mannose binding lectin (MBL) with mannose containing glycopeptides and the resultant potential impact on invasive fungal infection

Abstract: Mannnose-binding lectin (MBL) binds oligosaccharides on the surface of microorganisms to form complexes that activate the complement cascade and facilitate phagocytosis. Teicoplanin and dalbavancin glycopeptide antibiotics possess N-acetyl glucosamine and mannose oligosaccharides that may bind MBL. Pharmaceuticals capable of binding to MBL may decrease clearance of significant pathogens such as yeast. An invasive candidemia murine model was utilized to evaluate differences in survival between mannose- and teic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…MBL was well documented to have the ability to bind with high affinity to the mannose moiety of Candida species, and activate the complement system in complex with MASP, and greatly accelerate the C3/C4-mediated opsonophagocytosis of fungal pathogens [5], [6], [17], [18]. In this study, we demonstrated that the inhibitory effect on the phagocytosis of C. albicans by neutrophils caused by blockage of Dectin-1 was compensated by the exogenous MBL in a dose-dependent manner (Figure 2A–2F).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MBL was well documented to have the ability to bind with high affinity to the mannose moiety of Candida species, and activate the complement system in complex with MASP, and greatly accelerate the C3/C4-mediated opsonophagocytosis of fungal pathogens [5], [6], [17], [18]. In this study, we demonstrated that the inhibitory effect on the phagocytosis of C. albicans by neutrophils caused by blockage of Dectin-1 was compensated by the exogenous MBL in a dose-dependent manner (Figure 2A–2F).…”
Section: Discussionmentioning
confidence: 99%
“…FITC-labeled C. albicans was prepared by labeling the fresh HK- C. albicans with FITC according to the methods described previously [6], [18]. The homogeneous distribution of FITC- C. albicans was confirmed by flow cytometry assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The com-plement system can be activated through three pathways: the classical pathway (CP), the alternative pathway (AP), and the lectin pathway (LP). All three pathways can be activated by Candida (98,123,124). The opsonized Candida cells can be more efficiently ingested by phagocytes through the interaction between the CR3 and C3b, which is deposited on the Candida surface (62), or between the Fc receptor and the anti-Candida antibody (4).…”
Section: Soluble Factorsmentioning
confidence: 99%
“…Then the hypocomplementemia might be derived from such a heavy complement activation induced by immune complex formation. Some studies report that severe fungal infection such as candidiasis can cause complement activation and vasculitis [15,16]. To our knowledge, this is the first clinical report that referred to the direct association between mucor infection and complement activation via the lectin pathway.…”
Section: Iga ?mentioning
confidence: 82%